(untitled) (Bangladesh Journal of Livestock Research, 2016)
A total of 198 straight run day old ducklings of Bangladesh Livestock Research Institute (BLRI) developed native duck (named as Rupali and Nageswary) and local native duck genotypes were distributed among nine farmers of low laying areas of Kalihati Upazilla of Tangail district. Rupali and Nageswary ducklings were obtained from existing stock of BLRI and local native ducklings were collected from local farmers of the study area. After 12 weeks of age each farmers retained 10 female and 2 male ducks and sold away remaining ducklings. Farmers were instructed to supply 50g of balanced feed to their ducks in the morning and evening. Ducks were allowed to scavenge in the beel throughout the day. Data on: growth, feed intake, age at onset of lay, egg production rate, egg weight, mortality rate were recorded and cost-benefit was calculated. There found no significant difference on growth parameters, live weight gain, age at first laying or age at peak egg production among the duck genotypes. In the study highest live weight gain was found in Nageswary (1090 g) followed by Rupali (1058 g) and local native (912 g) duck at 8 weeks of age. Egg production rate of local native ducks (37.21%) was found significantly lower (P<0.001) compared to Rupali (50.67 %) and Nageswary (55.40 %). The mortality rate in local duck was significantly higher (P<0.05) compared to Rupali and Nageswary ducks. Rupali ducks produced heavier eggs (66.86g) followed by local native (62.20g) and Nageswary (57.22g) which differed significantly (P<0.05). Rupali ducks laid eggs of thicker shell (0.61mm) compared to other duck genotypes under study which was also varied statistically (P<0.05). Cost benefit analysis shows that earning both from Nageswary and Rupali was much higher than local native ducks. Higher egg production rate of Nageswary and Rupali duck has contributed for higher return. It is concluded that rearing Rupali or Nageswary ducks in the low laying rural areas with scavenging and supplementary feeding facility is more profitable than rearing local native ducks. Bangladesh J. of Livestock Res. 19(1-2): 18-23, Jan-Dec 2012